Study of Public Space Development Based on Preservation of Cultural Heritage Areas: Case Study of Muara Jambi Area - Graha Cahyadi, Farhan Rachmanda (UI Scholars Hub, 2025)
Background: The development of public spaces in cultural heritage areas has an important role in supporting the preservation of historical and cultural values, while improving the quality of life of the community around the cultural heritage. Aims: This study aims to examine the potential for developing public spaces that are in line with efforts to preserve the Muara Jambi Cultural Heritage area. Methods: The method used is qualitative-descriptive with conceptual-contextual orientation. Data collection techniques are carried out through systematic literature studies, document analysis, and triangulation through stakeholder statements. Data are analyzed using thematic analysis to identify relevant key elements. Results: The results of the study indicate that the development of public spaces in the Muara Jambi area can be carried out by integrating elements of cultural education, ecotourism, and sustainable community activities. Conclusion: Increasing accessibility, providing environmentally friendly facilities, and involving local communities are key factors for success. This strategy not only supports the preservation of cultural heritage areas, but also creates a space for social interaction that strengthens local cultural identity. These findings provide practical recommendations for tourism offices, local governments and cultural heritage area managers in designing inclusive and preservation-oriented public spaces.